RESEARCH OF THE PECULIARITIES OF THE MOTIVATION SPHERE OF FUTURE DOCTORS - Alla Stepanivna Borysiuk (Insight: the psychological dimensions of society, 2019)
The article presents a theoretical review and the results of an empirical study of the motivational sphere influence on cognitive activity and professional formation of a medical student. It was emphasized that the issue of motivation of medical students to choose the future profession and educational activities at the university is extremely important and relevant. It is noted that the performance of any activity is greatly influenced by the nature of motivation. Internal positive motivation increases the productivity of activity, gives the feeling of satisfaction, while negative and external decreases them, and then activity is perceived as coercion. Moreover the internal positive motivation for learning, self-improvement and professional growth itself can be considered as a professionally significant quality, especially when it comes to creative professions, including the one of a doctor. Personality orientation and the presence of strong positive motivation can be considered as factors of amplifying the significance of professionally ambitions. The influence of various types of motives on the success of professional training of a medical student is substantiated. The importance of taking into account the student's motivational sphere is shown in the application of teaching methods in order to implement a holistic approach to the professional training of future specialists. The level and quality of learning, abilities and practical skills of students depends hence greatly on the extent to which learning, as a process of obtaining a degree and personal self-improvement, is personally significant, backed up by internal positive motives that are formed from the family.The educational process in institutions of higher education should be oriented not only to the learning, but also to the development of the individual and, above all, to study and accounting its motivational sphere.